2020
DOI: 10.1186/s12913-020-05593-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between doctors’ presenteeism and job burnout: a cross-sectional survey study in China

Abstract: Background: It is necessary to examine doctors working with illness from a professional point of view, because it is not only related to their occupational health, but more importantly, will affect the treatment effect of patients and the overall medical level of the hospital. The purpose of this study was to explore the relationship between doctors' presenteeism and job burnout, and to identify other factors that are associated with presenteeism. Methods: A cross-sectional survey involving doctors (except for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…The job burnout of this study was investigated using the Chinese version of the Maslach Burnout Inventory–General Survey (MBI-GS), which has been widely used in Chinese medical staff, and has been shown to have good reliability and validity [ 25 ]. The MBI-GS of Chinese version consists of three dimensions and 15 items: emotional exhaustion (EE, five items), cynicism (CY, four items) and reduced personal accomplishment (PA, six items).…”
Section: Methodsmentioning
confidence: 99%
“…The job burnout of this study was investigated using the Chinese version of the Maslach Burnout Inventory–General Survey (MBI-GS), which has been widely used in Chinese medical staff, and has been shown to have good reliability and validity [ 25 ]. The MBI-GS of Chinese version consists of three dimensions and 15 items: emotional exhaustion (EE, five items), cynicism (CY, four items) and reduced personal accomplishment (PA, six items).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this model of equivalence between dimensions and items ignores the relationship between them, which may play a very important role in the development and maintenance of burnout [ 11 ]. Some scholars believe that each dimension should be calculated in a weighted manner [ 12 ]. In the calculation of the total score, emotional exhaustion accounted for 40%, cynicism and reduced personal satisfaction each accounted for 30% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars believe that each dimension should be calculated in a weighted manner [ 12 ]. In the calculation of the total score, emotional exhaustion accounted for 40%, cynicism and reduced personal satisfaction each accounted for 30% [ 12 ]. Some scholars believe that the scores of the three dimensions cannot be added at all; thus, each dimension should be calculated separately and a threshold standard should be established [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…High rates of presenteeism among the nurses decrease their performances, increases the patient safety risks, and cause negative results in healthcare institutions in time [26]. In the study which was conducted by Pei 2020 et al [27]. With healthcare workers, it was found that 86.8% of the participants had high presenteeism scale scores.…”
Section: Discussionmentioning
confidence: 99%